Properties of nanostructure copper (I) Iodide thin film for dye-sensitized solar cell / Mohammed Yusri Sharudin - Sharudin, Mohammed Yusri (2010)
This report presents the research on properties of nanostructure Copper (I) Iodide thin films for Dye-Sensitized Solar cell prepared by using sol-gel method at different molarities. The precursor used was chemically pure Copper (I) Iodide powder mixer with Acetonitrile which act as solvent at different molarities such as 0.01 M, 0.03 M and 0.05 M. The Cul thin films were deposited on the substrates by using spin coating technique. The thin films were also prepared at different annealing temperature that is T = 50°C, 75°C, 100°C, 125°C and 150°C. The influence of molarities and annealing temperature on the surface morphology, the electrical and the optical properties of the thin films was characterized by using Field Emission Scanning Electron Microscopy (FESEM), solar simulator I-V measurement and UVVIS spectroscopy respectively. For electrical properties, it was found that resistivity increased when the surface of the Cul thin films started to recombine and melt uniformly, hence the conductivity of Cul thin films decreased. For the surface morphology, the different molarities and annealing temperatures make the Cul particle increased in size, recombined and formed denser film.